Desentalisasi Fiskal dan Minimnya Pembangunan di Indonesia - Rahman, Fathur (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2012)
Fiscal decentralization policy is one of the mos t important part of the concept of decentralization. By fiscal decentralization, we could hope that each regional government could enforcing the development in their region. But, fiscal decentralization policy in field could not be implemented in a whole sector caused of political factor. Then, each regional government has a good financial capability since 2001 because they get a bog amount of fund transfer from the central government, but the allocation to development is very few. For example, there are still many broken road. This case may be caused by the transfer fund from the central government is allocated mostly to employement expenditure.